Rare bird documentation form for Lesser Black-backed Gull on the Mississippi River at Davenport, 1996 - Edwards, Chriset al (1996)
Rare bird documentation form for a Lesser Black-backed Gull on the Mississippi River at Davenport in Scott County, IA on January 7, 1996. Epson - sheet feed